Challenging Social Norm through Literature: Education, Inequality, and Sustainable Development - Sabtiana, Rela (Lamintang Education and Training Centre, in collaboration with the International Association of Educators, Scientists, Technologists, and Engineers (IA-ESTE), 2025)
Education plays a crucial role in shaping societal values and challenging structural inequalities. This paper explores how literature, particularly Shirley Jackson’s “The Lottery,” can be used as a tool to critically examine oppressive social norms within educational contexts. By applying Marxist and hyperrealist theories, the study analyzes how ritualistic violence in “The Lottery” mirrors real-world mechanisms of social control that sustain inequality. The paper argues that integrating literature into social sciences education can transform traditional learning approaches by encouraging students to question inherited norms and develop critical consciousness. This interdisciplinary approach aligns with SDG 4 (Quality Education) and SDG 10 (Reduced Inequalities), advocating for education that empowers learners to actively engage in social transformation. The findings suggest that a literature-based pedagogy in social sciences can drive a deeper understanding of systemic issues and contribute to a more just and sustainable society. The study further emphasizes the need for an interdisciplinary teaching approach where literature is used to foster critical thinking and inspire active participation in social change, supporting the realization of sustainable development goals.